Evaluation of some quality standards in the Faculty of Physical Education - University of Baghdad From the perspective of faculty members - Raheem , Waad (Journal of Physical Education, 2012)
The research aims to identify the concept of quality and the concept of quality standards in educational institutions, as well as evaluating some quality standards in the Faculty of Physical Education - University of Baghdad, from the perspective of faculty members. The population of research to all members of the faculty of the College of Physical Education - University of Baghdad for the academic year 2011-2012 and of the number (208) faculty member, was chosen as a random sample of members of the faculty’s (100) and distributed them to identify the study and collection of them ( 75) questionnaire, and ruled out (25) to identify the lack of suitability to be a final sample size (75) faculty member. The researcher adopted Form questionnaire’s (a unit to ensure quality and performance of university at Baghdad University - Faculty of Physical Education), which contain (495) paragraph as the initial and the number of fields (11), it has been selected three areas and to agree on (45), paragraph and by agreement (75 %). The most important results are based organization specific instructions to determine the hours of teaching for faculty members according to degrees. The Foundation is also keen to accept students in the preparation of preliminary studies and plans in accordance with the assessments. The most important recommendations is the need to encourage the institution of faculty members to publish in scientific journals of the Court. And also the need to explore students’ views of the institution in evaluating the performance of faculty members.